Knowledge and Practice of Contact Lens Wear and Care among Medical Students of University of Malaya - Tajunisah, Iqbal; Reddy, S.C.; Phuah, S.J. (Malaysian Medical Association, 2008)
The knowledge related to contact lens wear and practice care of contact lenses among medical students of University of Malaya was assessed through a structured questionnaire. One hundred and twenty one contact lens wearers participated in this study. Majority of contact lens wearers were females (106, 87.6%); the duration of contact lens wear varied from less than six months to two years or more; 53 (43.8%) cited cosmetic purpose for wearing contact lens; 16 (13.2%) were not removing their contact lenses prior to sleeping at night. Despite 107 (88.4%) were aware of complications of contact lens usage, only 102 (84.3%) were adhering strictly to proper hygiene and contact lens care; and 17 (14%) continued wearing in spite of eye symptoms. Forty seven (38.8%) students sought ophthalmic consultation for eye problems. Improper practice of contact lens wear and care even in educated users such as medical students could increase the risk of complications. Therefore, a need for more education to the consumers is desired.